PEMANFAATAN APLIKASI POINT OF SALES BERBASIS WEB PADA MINI MARKET DI KECAMATAN PANYABUNGAN KABUPATEN MANDAILING NATAL - Harahap, Seprida Hanum (Scenario (Seminar of Social Sciences Engineering and Humaniora), 2021)
To improve the economy in a region, it requires efforts from all factors, one of which is the productive economy, namely Small, Micro and Medium Enterprises (UMKM). One of the activities of UMKM that is of concern is the modern market business or mini market, where products from the mini market are selected by the buyer directly and then paid through the cashier. Several well-known mini markets, such as Indomaret and Alfamart, have used a transaction recording application known as Point Of Sale. However, some districts do not allow the presence of these two companies. The presence of these two companies is believed by some district governments to kill the UMKM market in the local area. So that there are growing mini markets that have developed in the area. The presence of mini markets in the district is not accompanied by accurate recording of transactions. So that many of these UMKM still have problems. Along with that, several things are needed such as using an application that aims to make it easier for UMKM players in marketing their products. The same is the case with these well-known supermarket companies, so that the competitiveness and selling value and accountability of the business can be maintained.